Synthesis of an anionic Au(I) hydroamination precatalyst supported by charged hydrido-carboranyl phosphine ligands. (1st December 2018) - Kleinsasser, Jack F.; Lee, Sarah E.; Lugo, Christopher A.; Tej, Varun; McArthur, Scott G.; Lavallo, Vincent
Graphical abstract: An anionic Au(I) complex supported by two charged carboranyl phosphines is reported. Its catalytic activity for the hydroamination of alkynes is investigated and compared to the most active known system. Abstract: Herein is reported the synthesis of an anionic gold complex bearing two charged hydrido carboranyl phosphine ligands. The compound is fully characterized by multinuclear NMR spectroscopy, high resolution mass spectrometry, as well as a single crystal X-ray diffraction study. In addition, we probe this compound's ability to catalyze the hydroamination of alkynes and compare its behavior to a related highly active catalyst supported by a perchlorinated carboranyl phosphine.